Generating a New Convolution Function From Mittag-Leffler and Koebe Functions - Ali Halil Ghathith; Ahmed Mohammed Ali; Mohammed Thanoon Al-Neima (International Journal of Mathematics and Mathematical Sciences)
This paper describes the generation of a new function using the convolution process for a Mittag-Leffler function of one parameter α and a Koebe function. The resulting function is characterized by many properties, the most important of which is that it is convergent. This paper finds many recursive relations, finds functions that are difficult to find using the inverse Laplace transform by analytic and mathematic programs, and finds several special cases. In addition, new formulas for the resulting function are obtained after using operations known as multiplication with a variable or an exponential function, division, integration, and differentiation.